2009
DOI: 10.1007/s00040-009-0023-3
|View full text |Cite
|
Sign up to set email alerts
|

Apis mellifera evolutionary lineages in Northern Africa: Libya, where orient meets occident

Abstract: The distribution of various evolutionary lineages of Apis mellifera subspecies in Africa is still controversial. We sampled honeybees from eight coastal locations and three Saharan oases in Libya and analyzed mtDNA variability with restriction fragment length polymorphisms and the sequence of the tRNAleu-cox2 intergenic region. Haplotypes belonging to the oriental O evolutionary lineage, including four which are newly described, were detected in all investigated locations. Haplotypes belonging to the European … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
1
12
0
1
Order By: Relevance
“…Phylogeographic studies using molecular markers are also uncovering cryptic diversity [e.g. Apis mellifera (El Niweiri & Moritz, ; Shaibi et al ., ); Acanthodactylus spp. (Fonseca et al ., ); Ptyodactylus spp.…”
Section: Distribution Of Biodiversitymentioning
confidence: 99%
“…Phylogeographic studies using molecular markers are also uncovering cryptic diversity [e.g. Apis mellifera (El Niweiri & Moritz, ; Shaibi et al ., ); Acanthodactylus spp. (Fonseca et al ., ); Ptyodactylus spp.…”
Section: Distribution Of Biodiversitymentioning
confidence: 99%
“…These surveys have provided a largely concordant grouping of diversity into four major evolutionary lineages, whose designations are roughly coincident with their geographical ranges, namely: the African (A), the Middle Eastern (O), the eastern European (C), and the western European (M). Current distribution of these lineages is largely parapatric with contact zones identified in Italy (Franck et al 2000), Turkey (Kandemir et al 2006), Libya (Shaibi et al 2009a), and in the Iberian Peninsula (Smith et al 1991;Franck et al 1998;Arias et al 2006;Miguel et al 2007;Cánovas et al 2008). Special attention has been paid to the Iberian contact zone, which has been examined with biparental and, more extensively, with maternal markers (Smith et al 1991;Franck et al 1998;Garnery et al 1998;Arias et al 2006;Miguel et al 2007Miguel et al , 2011Cánovas et al 2008Cánovas et al , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Although, mitochondrial DNA analyses showed two mitotypes of the evolutionary lineage O (Shaibi et al 2009b), the small F st values among colonies within Kufra suggests that the population is very homogeneous indeed. The locations open to migratory beekeeping (Brak and Coast) showed significantly higher population substructuring at the colony level, suggesting that the queens' mates represent a more biased sample than those drones mating the queens in Kufra.…”
Section: Gene Diversity and Population Differentiationmentioning
confidence: 89%
“…Recently, Shaibi et al (2009a) suggested that remote honeybee populations in the Libyan deserts are autochtonous populations that can be readily identified as distinct morphotypes, very different from adjacent subspecies of A. mellifera. Also mitochondrial DNA analyses suggested that these bees are old relic populations from a time when honeybees where abundant all over North Africa (Shaibi et al 2009b) suggesting that the bees of the Oasis Kufra had not been introduced by man and indeed is an endemic population confined for much more than 5,000 years in an area of 88 km 2 and separated by over 1,000 km of sand desert to the next viable habitat for honeybees.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation